Internal Locus of Control, Dukungan Teman Sebaya, dan Status Sosial Ekonomi Keluarga Terhadap Kematangan Karir Mahasiswa Tingkat Akhir - Herisdawati, Yuni; Arita, Sri (Politeknik Piksi Ganesha Indonesia, 2025)
This study aims to analyze the influence of internal locus of control, peer support, and family socio-economic status on career maturity among final-year students of the Faculty of Economics and Business, Universitas Negeri Padang, both partially and simultaneously. The research background is based on the phenomenon of low career maturity among students despite being in the final stage of their studies, as indicated by the lack of readiness to enter the workforce. This research employs a quantitative approach with an associative design. The population consists of all final-year students of the Faculty of Economics and Business, with a proportional random sampling technique used to determine the sample. Data were collected through questionnaires that had been tested for validity and reliability, and then analyzed using multiple linear regression. The findings of this study are expected to provide theoretical contributions to the development of career maturity studies, as well as practical benefits for students, faculty, and future researchers in formulating strategies to enhance graduates’ work readiness.